2012
DOI: 10.1021/ef300994m
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Carbonyl Compounds and Fine Particles Emitted by Combustion of Biodiesels in a Generator

Abstract: The main objectives of this study are the assessment of fine particles (PM2.5) and carbonyl compound emissions from an electrical generator fueled with biodiesels and the evaluation of the efficiency of a commercial 4-way catalytic converter toward these pollutants. Two different biodiesels were used: Soybean Oil fatty acid Methyl Esters (SOME) and Waste Cooking Oil fatty acid Ethyl Esters (WCOEE). Several biodiesel blends with petroleum diesel were tested (0%vol, 7%vol, 20%vol, and 50%vol). For all blends it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…They also generate air pollutants like automotive diesel engines. Therefore, studies on the environmental impact of diesel generators are rare because they are classified as non-road sources and would be subjected to emission and fuel regulations in the future [17], such as reducing the level of sulphur [18]. For this purpose, the exhaust emissions from diesel generators fueled by different alternative fuels have been investigated by Bugosh et al [19], Pereira et al [20] and Valente et al [21], and different trends have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…They also generate air pollutants like automotive diesel engines. Therefore, studies on the environmental impact of diesel generators are rare because they are classified as non-road sources and would be subjected to emission and fuel regulations in the future [17], such as reducing the level of sulphur [18]. For this purpose, the exhaust emissions from diesel generators fueled by different alternative fuels have been investigated by Bugosh et al [19], Pereira et al [20] and Valente et al [21], and different trends have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the relative concentration of components in unregulated emissions between conventional diesel combustion and PPCI was represented with the relative peak area by using semi-quantitative method in GC-MS software [25]. Some hydrocarbons, including olefins, alkynes, and cyclohexanes, are considered to be extremely toxic [33,34]. In this paper, for example, 28-Nor-17.alpha.…”
Section: Semi-quantitative Analysis On Unregulated Emissionsmentioning
confidence: 99%
“…A detailed description of the whole experimental set-up can be found in Refs. [9,21], thus only the main features are given here. The test rig used consists of the diesel generator, a fuel tank and an exhaust pipe equipped with sampling probes linked to different analyzers allowing the analysis of the exhaust composition, in term of gaseous and particulate pollutants.…”
Section: Emission Analysis: Equipment and Protocolmentioning
confidence: 99%
“…Under the same conditions, petrodiesel was also investigated as reference fuel, as well as blends of petrodiesel with crude BA or JC oil (50 wt.%). Studies testing power generators with biofuels, particularly NEVOs either converted into ethyl biodiesels or blended with petrodiesel, are still very scarce [1,2,9]. Thus, this work will contribute to bridge some gaps in this field in favor of agricultural machinery and deployment of cogeneration in general.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation